IDEOLOGY IN CHARLOTTE PERKINS GILMAN’S SHORT STORY “THE YELLOW WALLPAPER” BY USING GENETIC STRUCTURALISM APPROACH - Irmayani; sabaruddin; Rahma Melati Amir (LP2M Institut Agama Islam Muhammadiyah Sinjai, 2021)
Abstract The purpose of this paper is to analyse the Ideology in Charlotte Perkins Gilman’s Short story “The Yellow Wallpaper “by using genetic structuralism approach. This research used descriptive method. The primary data is Charlotte Perkin Gilman’s work or short story “The Yellow Wallpaper” published and printed in 1995 by Penguin books. The secondary data is reference, which has relation to do the topic of the research. Then, the data is collected and analyzed by using genetic structuralism approach which is focus of the analysis of intrinsic and extrinsic aspect. Extrinsic aspect involves Gilman’s biography as well as social contexts as reference to constitute certain ideology adopted by Gilman and Intrinsic aspect focused on plot, character and setting of “the yellow wallpaper.” The result shows that the homologous of Gilman’s ideology and “The Yellow wallpaper” is related to feminist ideology. Her social and personality background revealed that she is a feminist activist. Gilman propose how the women tries to free from patriarchy system is by using rational imagination. The main character of “The Yellow Wallpaper” is a woman; a new mother who suffer from post-partum depression. She is able to see that most of women are hide behind the domestic pattern. The result shows that a woman who got an oppression and subordination by patriarchy system tends to have mental disorder and depression.